Profile of Maternal Smokers Who Quit During Pregnancy: A Population-Based Cohort Study of Tasmanian Women, 2011–2013. Issue 5 (11th April 2017) - Frandsen, Mai; Thow, Megan; Ferguson, Stuart G.
Abstract: Introduction: Smoking remains the single-most significant preventable cause of poor pregnancy outcomes, yet around 12% of Australian women smoke during pregnancy. Many women are motivated to quit when they find out they are pregnant, yet few are successful. While previous studies have examined the profile of the maternal smoker compared to her nonsmoking counterpart (Aim 1), little is known about what differentiates women who quit during pregnancy to those who do not (Aim 2). Here, we present results from a study investigating the characteristics of women who were able to quit during pregnancy. Methods: Data were drawn from the Tasmanian Population Health database of women who had received antenatal care between 2011 and 2013 ( n = 14300). Data collected included age, relationship status and ethnicity of expectant mothers, antenatal details, mental health conditions, and drug use. Independent samples t tests were used to compare differences between women who had, and those who had not, quit during pregnancy. The 19.4% of women who self-reported as smoking in the first half (first 20 weeks) of their pregnancy were further grouped and analyzed comparing those who reported still smoking in the second half of their pregnancy (smokers: n = 2570, 92.4%) to those who quit (quitters: n = 211, 7.6%). Results: Quitters (57.8%) were more likely to be in a relationship than their non-quitting counterparts (49.6%, p = .022) and were less likely to suffer from postnatal depression (2.4% vs. 6.0%, p = .029). No other differences between quitters and smokers were observed. Conclusions: Determining the profile of women who are able to quit during pregnancy may be important to improve the relatively poor cessation rates among maternal smokers and may assist in more effectively targeting at-risk women. Implications: Smoking cessation interventions have traditionally targeted socially disadvantaged women, for good reason: the majority of smoking pregnant women fall into this category. However, despite the significant attention and resources dedicated to antenatal smoking cessation interventions, most are ineffective with only 7.6% of the present sample quitting smoking during pregnancy. This paper may assist in developing more effective antenatal smoking cessation interventions by more clearly describing the profile of maternal smokers who successfully quit during pregnancy. Specifically, this paper highlights the need to acknowledge and address women's relationship status and mental health in order to promote smoking cessation in pregnancy.